Self Leadership: Unveiling the Key Strategies for Personal and Professional Empowerment at SMP Ma’arif Batu - Alfenny, Derivaty Neo; Wardani, Fransisca Puspita; Romadlona, Nohan Arum; Yulyantika , Nadya Rindy; Qotrunnada, Qonita; Safitri, Revina; Azizah, Sherin Nisa (Inovasi Lokal, 2023)
Self-leadership is the practice of intentionally influencing one's own thoughts, feelings, and actions toward achieving personal and professional goals. This service aims to increase middle school students' understanding of self-leadership. The target of this service activity is grade 8 students at Ma'arif Batu Middle School with a total of 28 students. The method used in this activity is the socialization method, namely providing leadership material regarding self-leadership with the media used being PowerPoint to support the delivery of the material. As a process of assessing aspects of students' knowledge, a pre-test and post-test were carried out to measure the level of understanding of students' self-leadership before and after being given the material. Before being given the material, an average score of 55 was obtained, and it increased after being given the material with an average score of 77.14. The results of the pre-test and post-test stated that the material given to grade 8 students at Ma'arif Batu Middle School was useful in increasing students' knowledge regarding self-leadership. This service activity concludes that through socialization, providing material about self-leadership can increase understanding of personal strategies and professional empowerment for grade 8 students at Ma'arif Middle School in Batu.